THE PHENOMENON OF LANGUAGE CHOICE IN BLIMBING MARKET, MALANG. - Niken Yolanda Br Samosir; Rauzatul Jannah; Munawwir Hadiwijaya (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
The sociolinguistic study is one of the interdisciplinary branches of sociology and linguistics with the object of language study as a means to communicate in the community. One of which is language selection. This study discusses the choice of language used by sellers and buyers and the factors behind the choice of language used by sellers and buyers in Blimbing Market, Malang. In general, this research is descriptive qualitative research. The data collection stage in this study used the listening method and proficient method. The data analysis stage used intralingual and extra lingual equivalents, presenting the results of data analysis using informal methods. The results showed that the interaction between the seller and the buyer was very communicative. The language selection in Blimbing market, Malng occurred in three forms: code-switching, code-mixing, and a single language. The factors behind the choice of language are 1) participant, 2) conversation topic, and 3) function (purpose and objective) of speech. There are four types of the participant a) familiarity, b) age differences, c) ethnic background and language of speakers, and d) the presence of third parties